SPECIFIC FEATURES OF CHRONIC TONSILLITIS DURING PREGNANCY - V. N. Lokshin; D. E. Zhaysakova; S. K. Stanova (Scientific Journal of Pedagogy and Economics, 2019)
The effect of chronic tonsillitis during pregnancy on the course and outcome of pregnancy, the effect on the fetus is considered. Against the background of chronic tonsillitis, pregnant women develop not only various pregnancy complications, but also a negative impact on the development of the fetus and newborn, therefore timely treatment and prevention of this pathology during pregnancy is necessary.